Pengembangan Rencana Pelaksanaan Pembelajaran Model Inkuiri Terbimbing Berbantuan Goolge Sites pada Materi Getaran, Gelombang, dan Bunyi - Siti Fatimah; Tirtawaty Abdjul; Nova Elysia Ntobuo; Citron S. Payu (Ideas Publishing, 2023)
Assisted Guided Inquiry Model Google Sites supports and promotes learner independence during the learning process. This study aims to know the qualifications based on the effectiveness, practicality, and effectiveness of the aspects. The method used is the 4-D research and development (R&D) model. The results are as follows. 1) adequacy determined by expert verification, receipt of valid criteria; 2) Practice identified through implementation scored 84% on good criteria and learner response scored 82% on good criteria. This shows that the lesson plans meet practical standards. 3) Efficacy is determined by the activity of the learner who achieved 85% of her on good criteria and the learner s learning outcomes with the value N-gain of 0.62 on the criteria N-means gain. This indicates that the RPP is included in the valid criteria.